1996
DOI: 10.4315/0362-028x-59.5.502
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the Microbiological and Biochemical Quality of Raw Milk by Carbon Dioxide Addition: A Pilot-Scale Study

Abstract: Carbon dioxide treatment of refrigerated raw milk was evaluated as a method for extending storage life by inhibiting growth of psychrotrophic bacteria and other bacterial groups in raw milk. The effect of CO2 acidification followed by degasification and pasteurization on biochemical and microbiological properties of cold stored milk was studied on a pilot scale, Two CO2 treatments (acidification to pH 6.2 and to pH 6.0) were compared with a control (untreated) milk during 4 days of storage at 4°C. Total bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 0 publications
2
34
0
2
Order By: Relevance
“…The effectiveness of CO 2 in extending the storage life of raw milk and cottage cheese has been well established (Amigo et al, 1995;Hotchkiss, 1991, 1993;Espie and Madden, 1997;King and Mabbitt, 1982;Kosikowski and Brown, 1973;Maniar et al, 1994;Moir et al, 1993;Roberts and Torrey, 1988;Ruas-Madiedo et al, 1996;Ruas-Madiedo et al, 1998b). CO 2 treatment is already routinely used in commercial cottage cheese production in the US (Loss and Hotchkiss, 2003), and an unpublished scaled-up field trial of CO 2 treatment of raw milk showed a 4 day increase in storage life of the treated sample (Hotchkiss et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The effectiveness of CO 2 in extending the storage life of raw milk and cottage cheese has been well established (Amigo et al, 1995;Hotchkiss, 1991, 1993;Espie and Madden, 1997;King and Mabbitt, 1982;Kosikowski and Brown, 1973;Maniar et al, 1994;Moir et al, 1993;Roberts and Torrey, 1988;Ruas-Madiedo et al, 1996;Ruas-Madiedo et al, 1998b). CO 2 treatment is already routinely used in commercial cottage cheese production in the US (Loss and Hotchkiss, 2003), and an unpublished scaled-up field trial of CO 2 treatment of raw milk showed a 4 day increase in storage life of the treated sample (Hotchkiss et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Carbon dioxide has emerged as an attractive preservative of raw milk as it is inhibitory against the growth of psychrotrophic bacteria including P. fluorescens (Hotchkiss et al, 2006;Loss and Hotchkiss, 2003;Martin et al, 2003), it is generally regarded as safe (GRAS), its treatment method is non-thermal, simple and economical, and it does not have adverse effects on the nutritional content of milk (Loss and Hotchkiss, 2003;Ruas-Madiedo et al, 1996;Sierra et al, 1996). The effectiveness of CO 2 in extending the storage life of raw milk and cottage cheese has been well established (Amigo et al, 1995;Hotchkiss, 1991, 1993;Espie and Madden, 1997;King and Mabbitt, 1982;Kosikowski and Brown, 1973;Maniar et al, 1994;Moir et al, 1993;Roberts and Torrey, 1988;Ruas-Madiedo et al, 1996;Ruas-Madiedo et al, 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of CO 2 in shelf-life extension has been well established in raw milk and cottage cheese (Amigo et al, 1995;Chen andHotchkiss, 1991, 1993;Espie and Madden, 1997;King and Mabbitt, 1982;Kosikowski and Brown, 1973;Maniar et al, 1994;Moir et al, 1993;Roberts and Torrey, 1988;Ruas-Madiedo et al, 1996;Ruas-Madiedo, Bascarán, et al, 1998) and has already been adopted in commercial cottage cheese production in the US (Loss and Hotchkiss, 2003). However, there have been no studies on carbonation of whey, so it would be of interest to test the potential of CO 2 to act as a whey preservative.…”
Section: Introductionmentioning
confidence: 99%
“…Resultados parecidos foram obtidos por Ruas-Madiedo et al (1996), onde o leite tratado com CO 2 reduziu em 1 a 1,5 logaritmos o crescimento de mesófilos. Ma, Barbano e Santos (2003) constataram que ao adicionar 1500 ppm de CO 2 ao leite cru, houve uma diminuição de 1 a 2 ciclos logarítmicos na contagem de mesófilos e de 2 ciclos logarítmicos na de psicrotróficos após 21 dias de armazenamento a 4 °C.…”
Section: Resultsunclassified
“…A redução do pH do leite de 6,8 para 6,0 com CO 2 causou uma inibição de 1,41 log 10 UFC/mL em psicrotróficos após 4 dias de armazenamento a 7 ºC (SIERRA et al, 1996). A mesma redução de pH diminuiu a contagem de psicrotróficos lipolíticos em 1 log 10 UFC/mL após 4 dias a 4 ºC (RUAS -MADIEDO et al, 1996 (Tecnal,modelo TE 184,Brasil). Ao final da linha de gás conectou-se um dispersor de gás (Figura 1, F) feito de vidro Pyrex provido de placa porosa na extremidade inferior.…”
unclassified